Post-Brexit: Hate Crimes and Human Rights Violations in the UK - H. Çınar, Özgür (Border Crossing, 2025)
As discussion of the political, economic, social and cultural consequences of Brexit for the UK continues, this article will explore how Brexit has affected human rights. With hate crimes increasing after the EU Referendum, there is anxiety regarding human rights and the traditional British lifestyle, based on tolerance and pluralism. Therefore, this article will endeavour to find answers to these questions: will Brexit undermine fundamental human rights? Will the Government’s policies to tackle hate crimes and Brexit-linked human rights violations work? What is the best way to deal with hate crimes? .